Análise das concepções de meio ambiente de estudantes do ensino médio e adultos residentes na área de manancial Billings (Diadema, SP) - Silva, Cinthia Ferreira da [UNIFESP] (2017)
The term “conception of environment” is very useful nowadays. But after all, what is that term means? Considering the scope of relations and environmental education and its assumption, the conception of the environment is mentioned as an important concept to initiate a diagnosis in the communities, and it provides some planning of the Environmental Education practices. Between the practices, the emphasis itself is found in the involvement of the community with the issues around the environment. But when stimulations are promoted, they come from different lines or approaches of Environmental Education, the conceptions about environment are presented diversified. In that way it is possible to have the diagnoses of the reality of the environmental questions of a community located in protected area of spring in order to answer the assumptions of educational processes in those areas, this research was meant to bring the goals of identifying and analyzing the environmental conceptions of the residents directly related to the water resource - the Billings Dam in the neighborhood Eldorado, in the Diadema city –so that suggests the problematization of the questions about the region like a strategy that contributes to the development of education activities in order to improve the natural environment and the residents’ quality of life. The methodology used for this research was qualitative-quantitative approach, using content analysis of some questionnaires applied with closed and open questions (structured and semi-structured). The appliance of the questionnaires was initiated after the approval of the Ethics and Research Committee with the informed consent term addressed to the participants. The first stage of application was carried out with teenagers from 14 to 19 years old, high school students from two State schools in the Eldorado region. The main results of that first stage indicated that there is still low participation of the students in actions involving environmental subjects. As well as the conception of environment for that group refers just some simple elements of nature (fauna and flora, for example). The term "spring" has not been adequately considered, so it seems not to appear or belong in the context of environmental protection where that neighborhood is inserted. The second stage of the research, with adults who reside in the neighborhood, showed beyond that conception of environment bringing elements of nature, it came up as a second focus in order to relate it to the problems that they live with, like pollution for instance. The study indicated that there is still a long way to go through the educational process with the capacity of embracing different conceptions about environment, including the environmental problems that surround them, creating a critical view about it. When it comes to adult public, besides they contextualize the environmental issues around that region, it must be prioritized the environmental education actions are based on the involvement and participation of the community so that, they can get over their expectations related to the quality of life and the environment that surround them.